2014
DOI: 10.7314/apjcp.2014.15.21.9535
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Breast Cancer in the Eastern Mediterranean Region: A Systematic Review and Meta-Analysis

Abstract: Background: Identifying risk factors of breast cancer is a key point for preventive strategies to reduce the incidence. The aim of current study was to determine most important risk factors for breast cancer in the Eastern Mediterranean Region (EMR) using a systematic review. Materials and Methods: PubMed, Scopus, Web of Science till August 24, 2012 and the reference lists of all included studies were searched. Analytic studies which had reported odds ratios (OR), relative risk (RR) or required data to calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 43 publications
3
19
0
2
Order By: Relevance
“…Our review results were consistent with the results of other studies (6,10,(24)(25)(26)(27). The meta-analysis results of Namiranian et al (2014) were also consistent with the results of the present study. Their results demonstrated the pooled OR for the overweight women (25 < BMI < 30) was 1.71 (95%CI = 1.09 -2.68) and the risk of breast cancer in obese women (BMI > 30) was higher than women with normal BMI (pooled OR = 2.21, 95%CI = 1.71 -2.36) (11).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our review results were consistent with the results of other studies (6,10,(24)(25)(26)(27). The meta-analysis results of Namiranian et al (2014) were also consistent with the results of the present study. Their results demonstrated the pooled OR for the overweight women (25 < BMI < 30) was 1.71 (95%CI = 1.09 -2.68) and the risk of breast cancer in obese women (BMI > 30) was higher than women with normal BMI (pooled OR = 2.21, 95%CI = 1.71 -2.36) (11).…”
Section: Discussionsupporting
confidence: 82%
“…Another review by Namiranian et al on the risk factors of breast cancer in the Eastern Mediterranean Region (EMRO) demonstrated that overweightness and obesity increase the risk of breast cancer and this association was statistically significant (11).…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de a idade não ter apresentado diferença estatística quando feita comparação entre os gêneros masculino e feminino, pôde-se Perfil clínico dos pacientes atendidos em um ambulatório de fisioterapia em oncologia do município de São Paulo observar que a média de idade dos pacientes que se apresentaram no ambulatório de fisioterapia foi de 56 anos, portanto uma média elevada. Esse fato corrobora com outros estudos que relacionam a idade como fator de risco para o desenvolvimento do câncer 14,15 e ainda com estudos que associam o tratamento fisioterapêutico no pós-operatório do câncer de mama em uma população com a faixa etária aproximada com a encontrada nos resultados do presente estudo 16 . Em contrapartida, apesar de a idade não ter apresentado diferença entre os gêneros, outra característica da população atendida que apresentou diferença significativa foi o IMC, o que era esperado devido à diferença significativa também encontrada no gênero dos pacientes.…”
Section: Discussionunclassified
“…Em contrapartida, apesar de a idade não ter apresentado diferença entre os gêneros, outra característica da população atendida que apresentou diferença significativa foi o IMC, o que era esperado devido à diferença significativa também encontrada no gênero dos pacientes. Considera--se que taxas elevadas de IMC estejam relacionadas ao aumento do risco para desenvolvimento do câncer 15 , como apontado no estudo de Montazari, et al 17 , que verificou diferença significativa (p = 0,004) no IMC do grupo com câncer de mama que apresentou média de 27,9 ± 3,9 kg/m 2 comparado à média do IMC do grupo controle de 26,3 ± 4,3 kg/m 2 . Os dados de gênero, IMC e idade corroboram com Ricci, et al 10 , que verificaram 196 mulheres brasileiras com câncer de mama, tendo a idade comparável à amostra do presente estudo, assim como IMC, que mostrou sobrepeso e obesidade, tendo a quimioterapia em determinados regimes como fator associado ao aumento de peso.…”
Section: Discussionunclassified
“…In a systematic review in 2014, Namiranian et al showed that a first pregnancy after 30 years of age and nulliparous women are strongly associated with the risk of breast cancer. 24 The prolonged interval between menarche and first pregnancy is associated with HR+ breast cancer, and a short interval between these events is related with TNBC. 10 Mesharam et al explained that experiencing menopause at an age of ≥50 years compared with women who had menopause before 45 years of age is associated with a 7.9-times greater risk of developing breast malignancies.…”
Section: Prolonged Interval Between Menarche and First Pregnancymentioning
confidence: 99%